Next-Generation Firewall Design Using an Intrusion Prevention System (IPS) Method for Securing the Web Portal Server of Universitas Bina Darma - Viren Pranata (Institute of Information Technology and Social Science (IITSS), 2025)
Network security is a crucial requirement for digital communication systems, particularly for institutions that rely heavily on web-based services. The design and implementation of network security systems must address increasing cyber threats, particularly unauthorized access, malware infiltration, and Distributed Denial-of-Service (DDoS) attacks that disrupt service availability. This study aims to design a Next-Generation Firewall (NGFW) using an Intrusion Prevention System (IPS) to detect and prevent potential attacks on the Universitas Bina Darma web portal server. The research applies the Action Research Method through four structured stages: Diagnosing, Planning Action, Taking Action, and Evaluating Action. The system was developed and tested through vulnerability assessments, firewall configuration, and IPS rule implementation. The results show that the NGFW with IPS effectively blocks cyberattacks, secures system vulnerabilities, and provides real-time intrusion detection capabilities. The study concludes that implementing an NGFW with IPS significantly enhances server security and performance.